Experimental research on the characteristics of drag reduction and mechanical degradation of polyethylene oxide solution. Issue 8 (18th April 2021) - Dai, Xiaodong; Li, Bing; Li, Lei; Yin, Shuming; Wang, Tao
ABSTRACT: Polymer drag reduction agents are easy to degrade during application. The drag reduction and mechanical degradation characteristics of polyethylene oxide were investigated in this research. A rotating disk apparatus evaluated the influence of molecular weight, concentration, temperature, mechanical degradation, and ultrasonic degradation. The experimental results showed that drag reduction property was influenced by the molecular formation, flow regime, and concentration. Rotating disk apparatus is similar to test circular system regarding reduction rate measurement for polyethylene oxide, where the rotating velocity was affected by the Reynolds number. The increase in temperature is not favorable for the drag reduction of polyethylene oxide, because of the more cluster formation caused by molecular motion strengthening. Simultaneously, polyethylene oxide with bigger molecular weight and hydraulic volume would show lower optimum concentration than smaller molecular weight. Also, the mechanical and ultrasonic degradation of polyethylene oxide solution were investigated. Due to the external transfer induced by free radical reaction energy, the polyethylene oxide with bigger molecular weight and longer chains are more likely to degrade, showing bad drag reduction effect.